Preparation and characterization of porous hydroxyapatite through polymeric sponge method - Iis, Sopyan; Jasminder, Kaur (Elsevier, 2009)
Porous hydroxyapatite samples were prepared via polymeric sponge method using commercial hydroxyapatite (HA) powder. The effects of sintering rate, stirring time and HA concentration on porosity, compressive strength and crystallinity of the porous bodies were evaluated. The study found that a faster sintering rate resulted in higher apparent density, higher compressive strength and better crystallinity. A longer stirring time also yielded the same results. 42 wt.% HA concentration was found to be the optimal concentration to achieve higher compressive strength and crystallinity, and lower porosity. The compressive strength of the porous bodies varied from 1.8 to 10.5 MPa for a porosity gradient of 34.3–59.8%. The results showed that the compressive strength is strongly dependent on porosity. Mechanically, the HA porous bodies developed in the study can be accepted as bone implants as the average compressive strengths are well within that of cancellous bone.